Implementasi Kurikulum 2013 di Sekolah Lingukngan Pondok Pesantren (Study Kasus Pondok Pesantren Darul Ulum Malang). - Oky Bagas Prasetyo (Universitas Muhammadiyah Jember, 2021)
The Senior High School of Darul Ulum Agung Islamic Boarding School has long implemented a national curriculum that is widely known as the 2013 Curriculum. This senior high school has thus addressed the government's wishes for implementing a national standard curriculum through integrating knowledge and student character. The present study is field research and employed a qualitative approach with a case-study design. Data collection included: a) participant observation. B) in-depth interviews, c) documentation, and d). data analysis. The findings indicate that the implementation of the 2013 Curriculum in the Senior High School of Darul Ulum Agung Islamic Boarding School are as follows: this school developed a plan that was congruent with the Boarding School’s vision and mission. Instructional planning in the school further integrated those commonly found in public schools as well as those found in Islamic boarding schools, leading to what was known as ‘an integral curriculum’. Furthermore, the implementation of the curriculum in the school divided the main PAI lesson into several ‘mulok’ (i.e., local contents) so that students became aware of specific subjects that exist in the field of PAI. In the classroom learning process, teachers combined traditional and modern learning systems. As well, in the evaluation session, the results of the scores from each ‘mulok’ were collected and put together before being averaged. The evaluation was also used as a reference for the planning and implementation phases of the target curriculum in the following academic year.